Career Cornerstones Establishing a Foundation for a Career in Healthcare - Nelson, Andrea M; Greene, Katherine (Open textbook library., 2023)
Welcome to Career Cornerstones: Establishing a Foundation for a Career in Healthcare. This book was created for students entering their respective health profession’s program. This book is designed to help students be successful not only in their health profession’s educational program, but also as they start to intern or work in healthcare settings.